Potentials to breed for improved fibre digestibility in temperate Czech maize (Zea mays L.) germplasm - Manfred Schönleben; Joachim Mentschel; Luboš Střelec (Czech Journal of Genetics and Plant Breeding, 2020)
Cell wall digestibility is an important quality trait of modern silage maize cultivars. The symbiotic relationship between microbes and ruminant livestock enables the efficient upcycling of otherwise for human consumption unsuitable rumen digestible fibre or cell wall components into highly nutritious milk and meat. Before entering the Czech National List of Plant Varieties, new silage maize germplasm is extensively tested for different cell wall digestibility parameters. Recently published, the undigestible neutral detergent fibre (uNDF) cell wall digestibility approach promises even greater practical relevance. The aim of our study was, therefore, to assess the potential of the uNDF method, compared with current standard procedures, using a vast set of official Czech plant variety trial evaluations and Czech silage analyses from the 2018 cropping season. The uNDF method yielded a twice as high phenotypic standard deviation, compared with the current standard approaches. This is good news for plant breeders, official variety testing organisations, and farm professionals alike, enabeling faster variety improvement and simpler variety selection. On the other hand, due to the low differentiation potential, we discourage the use of the absolute lignin content when selecting for digestible silage maize varieties. Since between the digestibility traits enzymatic soluble organic substance (ELOS) and cellulase digestibility (DCS), a Pearson correlation close to one was observed, the substitution of one of these analytics by the uNDF method, may render valuable additional information in a highly economical manner.